Watchful surgery in asymptomatic mitral valve prolapse - Carpenito, Myriam; Gelfusa, Martina; Mega, Simona; Cammalleri, Valeria; Benfari, Giovanni; De Stefano, Domenico; Ussia, Gian Paolo; Tribouilloy, Christophe; Enriquez-Sarano, Maurice; Grigioni, Francesco (Frontiers in Cardiovascular Medicine, 2023)
The most common organic etiology of mitral regurgitation is degenerative and consists of mitral valve prolapse (MVP). Volume overload because of mitral regurgitation is the most common complication of MVP. Advocating surgery before the consequences of volume overload become irreparable restores life expectancy, but carries a risk of mortality in patients who are often asymptomatic. On the other hand, the post-surgical outcome of symptomatic patients is dismal and life expectancy is impaired. In the present article, we aim to bridge the gap between these two therapeutic approaches, unifying the concepts of watchful waiting and early surgery in a “watchful surgery approach”.